2008
DOI: 10.1590/s0102-311x2008000700015
|View full text |Cite
|
Sign up to set email alerts
|

Estudo exploratório sobre aleitamento materno entre escolares de quinta série do Ensino Fundamental

Abstract: O estudo avaliou conhecimentos, percepções, crenças e vivências em relação ao aleitamento materno em 564 escolares, de ambos os sexos, da quinta série do Ensino Fundamental. O questionário usado continha 25 questões objetivas. Aplicou-se o teste de qui-quadrado e teste t, considerando a amostragem por conglomerado. Os escolares consideraram o leite materno o melhor alimento para o bebê, mas 60% optariam pela amamentação exclusiva de seus filhos. Menos de 20% responderam que a criança pode mamar até dois anos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
4
1
0
4
Order By: Relevance
“…In additi on, while playing, children do not talk to their friends about mothers breastf eeding their babies. These fi ndings are similar to that of other studies (4,10) , which had found, respecti vely, that only a small percentage of the interviewees always pretended to breastf eed or alternated between pretending to breastf eed and giving a bott le when playing with their dolls and that in childhood games, less than half the female scholars and very few male scholars reported that the dolls were breastf ed. The results involving the toys were not surprising, because children follow the model that is transmitt ed to them.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In additi on, while playing, children do not talk to their friends about mothers breastf eeding their babies. These fi ndings are similar to that of other studies (4,10) , which had found, respecti vely, that only a small percentage of the interviewees always pretended to breastf eed or alternated between pretending to breastf eed and giving a bott le when playing with their dolls and that in childhood games, less than half the female scholars and very few male scholars reported that the dolls were breastf ed. The results involving the toys were not surprising, because children follow the model that is transmitt ed to them.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, it was found that most Portuguese children were not used to seeing women breastf eed outside of their family environment, i.e., in public, and this experience could cause those children to develop a breastf eeding perspecti ve with reservati ons and taboos. These results are similar to those found in other studies (4,10,12) , confi rming that although children state they would like to breastf eed later in life, they would be embarrassed to do that in public.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…School is the main institutionalized environment of the pedagogic and teaching-learning process, of socialization and growth, where one acquires cardinal health-promoting values. Yet, for this to happen, the school curriculum needs to be flexible, the school staff needs to be trained and health professionals and the local community need to collaborate 24,25 .…”
Section: Discussionmentioning
confidence: 99%